Adaptability and phenotype stability of Arabica coffee cultivars in Minas Gerais, Brazil - Botelho, Cesar Elias; Rezende, Juliana Costa de; Carvalho, Gladyston Rodrigues; Carvalho, Alex Mendoça de; Andrade, Vinicius Teixeira; Barbosa, Cintia Reis (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the phenotypic adaptability and stability for grain yield of the Catuaí group of coffee cultivars by the method Annicchiarico. The experiments were installed and carried out in the counties of Três Pontas, Campos Altos and Capelinha, Minas Gerais state, Brazil. The experiments were carried out in a randomized complete block design, with four replicates and six plants per plot. The treatments were constituted by 15 cultivars of the Catuaí group and five controls. The grain yield evaluations were performed in the six harvests from 2003/2004 to 2008/2009 growing seasons. Then, the joint analysis of the three localities and the evaluation of cultivars adaptability and stability were performed. The parameters floating beans and high sieve grains were carried out considering the 2008/2009 harvest. The cultivars Catuaí Vermelho IAC 15, Catuaí Amarelo IAC 30, Catuaí Amarelo IAC 62 and Catuaí Vermelho IAC 72 were the most promising because they allied higher stability and adaptability in favorable and unfavorable environments with mean high yield. The cultivars Catuaí Vermelho IAC 100, Catuaí Amarelo IAC 86, Rubi MG 1192 and Catuaí Vermelho IAC 144 have the highest percentage of bean size grains. All the cultivars showed low percentage of floating grains.